2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--17412
|View full text |Cite
|
Sign up to set email alerts
|

Academic Preparation for the Global Engineer

Abstract: He obtained both his baccalaureate and master's degrees from LSU ME and his doctorate from Purdue University's School of Mechanical Engineering. He has been actively engaged in teaching, research and curricula development since joining the LSU faculty in 1988. As Associate Dean, he has acquired funding from NSF to support the development of several initiatives aimed at improving student retention and graduation rates as well as supporting faculty with development with effective learning and teaching pedagogies. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The Klein-Gardner and Walker [4] survey found a range of 2.8 to 4.3 (5 point scale) for importance of their categories with the five highest being; 1) ability to communicate across cultures, 2) the ability to appreciate other cultures, 3) a proficiency working in or directing a team of ethnic and cultural diversity, 4) the ability to effectively deal with ethical issues, and 5) possessing understanding of cultural differences in engineering work. Based on 38 responses (not intended to be statistically significant) to a survey of a variety of engineering alumni and fewer than 10 senior faculty members who had engineering experiences on a global basis, Waggenspack, et al [10] found their top three items to be "understanding of global cultural diversity", "oral, written, and visual communication skills", and "ability to work harmoniously and efficiently in diverse group settings".…”
Section: Study Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Klein-Gardner and Walker [4] survey found a range of 2.8 to 4.3 (5 point scale) for importance of their categories with the five highest being; 1) ability to communicate across cultures, 2) the ability to appreciate other cultures, 3) a proficiency working in or directing a team of ethnic and cultural diversity, 4) the ability to effectively deal with ethical issues, and 5) possessing understanding of cultural differences in engineering work. Based on 38 responses (not intended to be statistically significant) to a survey of a variety of engineering alumni and fewer than 10 senior faculty members who had engineering experiences on a global basis, Waggenspack, et al [10] found their top three items to be "understanding of global cultural diversity", "oral, written, and visual communication skills", and "ability to work harmoniously and efficiently in diverse group settings".…”
Section: Study Developmentmentioning
confidence: 99%
“…International Affairs 5 Competencies [9] Dimensions of Global Competence [4] To succeed in today's global workforce, an engineer must [10] 1 Ability to work effectively in international settings.…”
Section: Table 1 Global Competencies For Engineering From the Literaturementioning
confidence: 99%
“…Engineering programs are partially responsible to provide the needed skills so that students will be successful upon graduation. This challenge does require periodic review [2]. Are universities and engineering programs doing enough?…”
Section: Introductionmentioning
confidence: 99%